ANALISIS PERAMALAN PRODUKSI SUSU BERBAGAI TERNAK PERAH DI INDONESIA MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Danang Nur Cahyo; Krismiwati Muatip; Afduha Nurus Syamsi; Hermawan Setyo Widodo; Merryafinola Ifani (ANGON: Journal of Animal Science and Technology, 2022)
metabolized by the human body. There are various dairy livestock spread around Indonesia specifically dairy cattle, dairy goats, buffalo, and sheep. This research aimed to forecast the milk production of various dairy livestock in Indonesia until 2028. The research method of this study was the secondary data method utilizing secondary data from the Food and Agriculture Organization (FAO) of the United Nation. Data used in this study was milk production of Indonesia from various dairy livestock in tonnes from 2012-2021. The Autoregressive integrated moving average (ARIMA) method was used to forecast milk production in Indonesia. The (p,d,q) value for the milk production forecast of dairy cattle, dairy goat, buffalo, and sheep were (1,1,1), (2,1,1), (0,0,1), and (1,1,1) respectively. Milk production for cows, goats and sheep is predicted to continue to increase until 2028, while buffalo milk production is predicted to decrease. Milk production from various dairy livestock besides dairy cattle has great potential to develop so as to create diversity in fulfilling the needs of dairy products in Indonesia.